KOMPETENSI PENGADILAN AGAMA DALAM PENYELESAIAN SENGKETA PERBANKAN SYARIAH BERDASARKAN UNDANG-UNDANG NOMOR 3 TAHUN 2006 DI HUBUNGKAN DENGAN PENYELESAIAN SENGKETA PERBANKAN SYARIAH PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 93/PUU-X/2012 - Moh Sutoro (Jurnal Surya Kencana Dua : Dinamika Masalah Hukum dan Keadilan, 2016)
The year 2006 is seen in the most revolutionary in the history of the existence of religious courts in the Indonesian legal system. Delegation of authority to examine, decide and resolve syariah economic case to the Religious Court signaled recognition of the existence of religious courts as well as the realization of the desire of the majority, even all Muslims in Indonesia to resolve the dispute in accordance guidance Shari'a. However, in practice before the judicial reviewe Act No. 21 of 2008 concerning Islamic banking, which in practice contains legal uncertainty because of the problem stems from differences in interpretation in deciding which forum has the authority to resolve disputes Islamic banking at hand that is the Choice of Forum and the Choice of law which in turn raises the formulation of legal uncertainty. Keywords: Competence, Dispute Resolution, legal certainty